2022
DOI: 10.54099/ijibmr.v2i2.387
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Performance and Their Impact on Firm Value in the Building Construction Industry Sub-Sector

Abstract: This study aims to analyze the effect of intellectual capital, managerial ownership, company size and company financial performance on firm value. This research was conducted at building construction industry sub-sector companies listed on the Indonesia Stock Exchange for the observation period from 2017 – 2021. A total sample of 9 companies was obtained using a purposive sampling technique. This study used panel data regression analysis with STATA 17 software. The results showed that intellectual capital had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The results of this study do not support thes ignalling theory and are not in line with Kurfi et al (2017), Sudiyatno et al (2020) and Sugosha and Artini (2020) who found that company size has a positive and significant effect on the company's financial performance. But this study agrees with Hasanah and Enggariyanto (2018) and Salim et al (2022) which found that company size has a negative and significant effect on the company's financial performance. Large companies should have greater opportunities to expand their business, so that they will generate higher profits.…”
Section: E Discussionsupporting
confidence: 90%
“…The results of this study do not support thes ignalling theory and are not in line with Kurfi et al (2017), Sudiyatno et al (2020) and Sugosha and Artini (2020) who found that company size has a positive and significant effect on the company's financial performance. But this study agrees with Hasanah and Enggariyanto (2018) and Salim et al (2022) which found that company size has a negative and significant effect on the company's financial performance. Large companies should have greater opportunities to expand their business, so that they will generate higher profits.…”
Section: E Discussionsupporting
confidence: 90%